Even the normal is abnormal: N-heterocyclic carbene C2 binding to a phosphaalkene without breaking the PC π-bond. Issue 5 (23rd November 2015) - Majhi, Paresh Kumar; Chow, Keith C. F.; Hsieh, Tom H. H.; Bowes, Eric G.; Schnakenburg, Gregor; Kennepohl, Pierre; Streubel, Rainer; Gates, Derek P.
Abstract : The reaction of MesPCPh2 with the least sterically demanding N-heterocyclic carbene (NHC = IMe) results in formation of the 'abnormal' (C 4 -substituted) 4-phosphino-NHC (1 ). Abstract : The reaction of MesPCPh2 with the least sterically demanding N-heterocyclic carbene (NHC = IMe) results in formation of the 'abnormal' (C 4 -substituted) 4-phosphino-NHC (1 ). In contrast, reaction with Me2 IMe gives the unprecedented 'normal' C 2 adduct, Me2 IMe → P(Mes)CPh2 (2 ). Particularly striking is the asymmetric and weak bonding of the NHC to the PC moiety in2 . DFT calculations indicate that the PC natural bond order in2 (1.54) still reflects significant π-character to the bond ( cf. MesPCPh2 : NBO = 1.98). Further computational analysis suggests that π-delocalization into the remote C-phenyl substituents is key to stabilizing the NHC adduct.